Stateless Transnational Migrant Children in South Africa: Implications and Opportunities for Social Work Intervention - Warria, Ajwang’ (African Human Mobility Review, 2021)
Migrant children who are vulnerable to statelessness are a growing at-risk populationworldwide, and in South Africa. Migrant children often travel unaccompaniedor become separated from their families during the journey, thus increasing theirvulnerability. These children are often denied their rights in countries of transit andresettlement and might even be detained due to lack of documentation. They are subjectto high levels of violence and status-exclusion within the migratory process. This paperconsiders statelessness in migrant children in South Africa, and undertakes a reviewof the literature to understand this phenomenon. The results show that a considerablenumber of migrant children in South Africa are at risk of statelessness. While allchildren may have roots that can be traced, situations and technicalities arise within themigration and registration framework that result either in children becoming statelessor at risk of becoming such. These children’s childhoods fall through the gaps as theylack a sense of belonging. They also have limited rights and none of the protection thatgoes with being recognized as nationals. Social workers are able to play a significantrole in assessing and determining if migrant children are either stateless or at risk ofbecoming stateless and offer appropriate intervention to help them realize their rights,potential and contributions.